Fruits and vegetables consumption and depressive symptoms: A population-based study in Peru - Wolniczak, Isabella (2017)
Objectives: Among different factors, diet patterns seem to be related to depression. The aim of this study was to evaluate the association between the consumption of fruits and/or vegetables and depressive symptoms. Methodology/Principal findings: A secondary data analysis was conducted using information from a population-based survey from 25 regions from Peru. The outcome was the presence of depressive symptoms according to the Patient Health Questionnaire (cutoff 15 to define major depressive syndrome); whereas the exposure was the self-reported consumption of fruits and/or vegetables (in tertiles and using WHO recommendation 5 servings/day). The association of interest was evaluated using Poisson regression models controlling for the complex-sample survey design and potential confounders. Data from 25,901 participants were analyzed, mean age 44.2 (SD: 17.7) and 13,944 (54.0%) women. Only 910 (3.8%; 95%CI: 3.5%–4.2%) individuals reported consuming 5 servings of fruits and/or vegetables/day; whereas 819 (2.8%; 95%CI: 2.5%–3.1%) had depressive symptoms. Those in the lowest tertile of fruits and/or vegetables consumption had greater prevalence of depressive symptoms (PR = 1.88; 95% CI: 1.39–2.55) than those in the highest tertile. This association was stronger with fruits (PR = 1.92; 95%CI: 1.46–2.53) than vegetables (PR = 1.42; 95%CI: 1.05–1.93) alone. Conclusions: An inverse relationship between consumption of fruits and/or vegetables and depressive symptoms is reported. Less than 5% of subjects reported consuming the amount of fruits and vegetables recommended by the WHO. There is a need to implement strategies to promote better diet patterns with potential impact on mental health. © 2017 Wolniczak et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.